Role of CD155/TIGIT in Digestive Cancers: Promising Cancer Target for Immunotherapy - Wang, Daijun; Gu, Yanmei; Yan, Xin; Huo, Chengdong; Wang, Guan; Zhao, Yang; Teng, Muzhou; Li, Yumin (Frontiers in Oncology, 2022)
The tumor microenvironment restricts the function and survival of various immune cells by up-regulating immune checkpoints, and participates in the immune escape of tumors. The development of immunotherapies targeting immune checkpoints, such as programmed cell death receptor 1 antibody and anti-cytotoxic T lymphocyte-associated antigen 4 antibody, has provided many options for cancer treatment. The efficacy of other immune checkpoint inhibitors is also under development and research. Among them, T cell immunoreceptor with Ig and ITIM domains (TIGIT) has shown excellent clinical application prospects. Correspondingly, poliovirus receptor (PVR, CD155), as one of the main ligands of TIGIT, is mainly expressed in various human malignant tumors and myeloid cells. CD155 interacts with TIGIT on natural killer cells and T cells, inducing tumor immune escape by mediating inhibitory immunomodulatory regulation. This study summarized the mechanism of CD155/TIGIT in regulating T cells and NK cells, its role in the occurrence and development of digestive system tumors, and its clinical application prospect, aiming to provide a new perspective for immunotherapy of digestive cancers.